ANALYSIS OF THE ABSORPTION OF EUROPEAN STRUCTURAL AND INVESTMENT FUNDS IN THE NEW MEMBER STATES OF CENTRAL AND EASTERN EUROPE - Bogdan Cosmin MOLDOVAN (Annals of the University of Oradea: Economic Science)
The present research aims to analyze the impact of the allocation of structural and investment funds on regional development in the new member states of Central and Eastern Europe and to identify pragmatic ways to improve absorption, useful in the future financial exercises. The aim of the research is to discover ways to improve the quality of life and increase the absorption of European funds in Central and Eastern Europe by: identifying the ways in which the countries of Central and Eastern Europe know how to benefit from and manage the structural funds, funds in which they participate by co-financing projects financed from the respective funds, identifying the main shortcomings of the systems, proposing viable solutions to improve the absorption model of the funds.